Characterization of aonla (Emblica officinalis) varieties under zero irrigation semi-arid conditions - SINGH, A K; SINGH, SANJAY; MAKWANA, PURNIMA (The Indian Journal of Agricultural Sciences, 2015)
A field study was conducted to differentiate the aonla (Emblica officinalis Gaertn) varieties for their vegetative and fruit characters under rainfed hot semi-arid ecosystem of western India during the years 2012-14. Among the cultivars, growth habit was observed upright spreading, tall upright, tall spreading, tall drooping and tall semi- spreading. The foliage was visualized as dense and sparse among all the cultivars. The leaflet colour (green to pale yellowish green), shape (oblong, oval oblong and elliptical), apex (obtuse and acute) also varied among the cultivars. The size of leaves in terms of length and breadth ranged between 1.25-1.47 cm and 0.23-0.37 cm, respectively. The time of fruit set and time of fruit maturity differed considerably among the varieties. The maximum fruit set (51.95%) and fruit retention (26.40%) were recorded in NA 7, whereas same was recorded minimum (36.21%) in Banarasi and Francis (11.34%).Variations in fruit shape, i.e. triangular, flattened oblong, flattened oval, and flattened round, whereas size of the fruit was observed as small large and medium among observed varieties. The highest fruit weight (33.90 g) and specific gravity (1.43) were found in Banarasi while these traits were recorded the lowest in Kanchan and Francis, respectively. The qualitative physico-chemical characters, viz. fruit juice content, acidity, pulp content, vitamin C content, TSS, TSS/acid ratio and stone weight ranged between 40.00-64.45%, 1.34-2.56%, 23.95- 31.95 g, 334.12- 461.76 mg /100gm , 8.00-11.50% and 3.61- 6.74 g and 1.97-2.08 g, respectively. The stone of the fruit also varied with respect to its shape (triangular and oval round) and size (large, medium and small) under rainfed hot semi-arid environment of western India.